Cross-cultural adaptation and psychometric evaluation of the Communication Function Classification System-Thai version for individuals with cerebral palsy in Thailand - Chaisook, Pim; Rattakorn, Phuanjai; Chinchai, Supaporn; Bunrayong, Wannipa (Journal of Associated Medical Sciences, 2025)
Background: Cerebral palsy (CP) is a neurodevelopmental disorder that affects motor functions and is often accompanied by impairments such as speech and communication challenges. Functional classification systems are increasingly used to describe daily activities and participation, aiming to guide comprehensive and effective treatment planning that improves patients’ quality of life. The Communication Function Classification System (CFCS) is a tool designed to describe communication functions in the daily lives of individuals with CP. Nonetheless, the absence of a Thai version of the CFCS highlighted the need for this study. Objectives: This study aimed to translate and culturally adapt the CFCS into Thai (CFCS-TH) and to evaluate its psychometric properties, including validity and reliability, in individuals with CP in Thailand. Materials and methods: The study was conducted in two phases: (1) cross-cultural adaptation and translation of the CFCS into Thai using a six-step forward and backward translation method, and (2) psychometric evaluation of the CFCS-TH, focusing on content validity, inter-rater reliability, and intra-rater reliability. Validity was assessed using the content validity index (CVI), while reliability was measured using weighted kappa statistics (ƙ). A total of 35 individuals with CP, aged 2-18 years, participated in the study. The raters included one speech-language pathologist (SLP), two physical therapists (PTs), and 35 parents, each of whom rated the level of communication function of the individuals with CP twice. Results: The cross-cultural adaptation of the CFCS to Thai was carried out by ensuring that the language and terminology were appropriate for Thai users while maintaining the conceptual integrity and purpose of the tool. The CFCS-TH translation steps included vocabulary and syntax selection, equivalency review, and revisions from translators, an expert committee, and pretest users, followed by approval from the instrument developers. The CFCS-TH demonstrated excellent content validity, with an item-level CVI and scale-level CVI of 1.0, indicating that the CFCS-TH could measure its intended construct. Inter-rater reliability was good between the SLP and PTs (ƙ=0.71), good between the SLP and parents (ƙ=0.66), and fair between PTs and parents (ƙ=0.55). When separating the data by the first and second classification rounds, agreement between the SLP and PTs remained good with a slight decrease (ƙ=0.73 and 0.69). The SLP-parent agreement remained consistently good across both rounds (ƙ =0.61 and 0.66), while the PTs-parents agreement improved from fair to good (ƙ=0.48 and 0.62). Intra-rater reliability was excellent for the SLP (ƙ=0.92) and very good for PTs (ƙ = 0.91) and parents (ƙ=0.86). Conclusion: The CFCS-TH is a valid and reliable tool for describing the communication functions of individuals with CP in Thailand. This tool provides a standardized framework for assessing communication performance to support clinical and research efforts aimed at intervention planning and improving the quality of life for individuals with CP.